2001
DOI: 10.3346/jkms.2001.16.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Clinical Survey of Behçet's Disease in Korea: the First Multicenter Study

Abstract: The prevalence of Behcet's disease is the highest in the East Asian and the Mediterranean countries. Behcet's disease is also distributed in the Asian countries, but the nationwide survey has not been performed in Korea yet. The Korean Study Group for Behcet's Disease, founded in 1999, conducted a multicenter, retrospective survey on epidemiologic and clinical features of the patients with Behcet's disease from 20 hospitals around the nation from 1997 to 1999. Of 3,497 patients, 1,527 were classified into comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
9
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 2 publications
5
65
9
1
Order By: Relevance
“…There was no patient with the visual loss due to the ocular lesions by BD during the follow-up, and those regimens seem to be effective for the treatment of Behc,et's uveitis. On the other hand, the prevalence of ocular lesions in the multicenter study in Korea (13) was much higher than those in the previous studies in Korea and in the current study, and this might be partly due to the use of the Japanese criteria that has emphasized the presence of ocular involvement.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…There was no patient with the visual loss due to the ocular lesions by BD during the follow-up, and those regimens seem to be effective for the treatment of Behc,et's uveitis. On the other hand, the prevalence of ocular lesions in the multicenter study in Korea (13) was much higher than those in the previous studies in Korea and in the current study, and this might be partly due to the use of the Japanese criteria that has emphasized the presence of ocular involvement.…”
Section: Discussioncontrasting
confidence: 53%
“…After the introduction of a disposable needle, the prevalence and intensity of a positive pathergy reaction have been described to decrease when compared with those by the non-disposable needle used in the pre-AIDS era (20). The current study showed a somewhat higher rate of a positive pathergy reaction than the multicenter study in Korea (13). We previously reported that the positive pathergy reaction was usually found in the active phase of the disease in individual cases with a positive reaction (6).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The clinical major symptoms of BD in Korean patients are oral ulcers (98.8%), skin lesions (84.3%), genital ulcers (83.2%), ocular lesions (50.9%), and minor symptoms including articular symptoms (38.4%), gastrointestinal symptoms (7.3%), neurological symptoms (4.6%), epididymitis (0.6%), and vascular symptoms (1.8%) (2). This wide range of clinical symptoms of BD probably reflects different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…It also occurs in Central and East Asian countries, such as Korea, Japan, and China. The incidence of BD in Korea has been increasing (13). The etiology of BD remains unclear, but genetic and environmental factors probably play a role in its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%